2023
DOI: 10.1002/adfm.202209421
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Solution to Icing by Acoustic Waves: De‐Icing, Active Anti‐Icing, Sensing with Piezoelectric Crystals, and Synergy with Thin Film Passive Anti‐Icing Solutions

Abstract: Icing has become a hot topic both in academia and in the industry given its implications in transport, wind turbines, photovoltaics, and telecommunications. Recently proposed de-icing solutions involving the propagation of acoustic waves (AWs) at suitable substrates may open the path for a sustainable alternative to standard de-icing or anti-icing procedures. Herein, the fundamental interactions are unraveled that contribute to the de-icing and/or hinder the icing on AW-activated substrates. The response towar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Compared to the high-temperature sensitivity of other wave modes (e.g., in Ref. [16]), de-icing with SAW, therefore, enables a much easier signaling approach, which is mostly insensitive to temperature and manageable with simpler electronics. This finding agrees well with those in Yang et al [15] Furthermore, Figure 3a,b presents S 11 spectra for water-loaded and glaze ice-loaded surfaces (>50% of the surface was wetted); no significant difference was observed between the coupling frequencies of the free substrate surfaces and the surfaces covered with water or ice in the two systems.…”
Section: Robust Saw Excitation For De-icing Of the Surface Beyond The...mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the high-temperature sensitivity of other wave modes (e.g., in Ref. [16]), de-icing with SAW, therefore, enables a much easier signaling approach, which is mostly insensitive to temperature and manageable with simpler electronics. This finding agrees well with those in Yang et al [15] Furthermore, Figure 3a,b presents S 11 spectra for water-loaded and glaze ice-loaded surfaces (>50% of the surface was wetted); no significant difference was observed between the coupling frequencies of the free substrate surfaces and the surfaces covered with water or ice in the two systems.…”
Section: Robust Saw Excitation For De-icing Of the Surface Beyond The...mentioning
confidence: 99%
“…In a recent work carried out both in laboratory and icing wind tunnel conditions, we have also demonstrated energy-efficient de-icing and prevention of icing with decreased surface ice adhesion using high-frequency shear acoustic vibrations in larger bulk piezoelectric substrates. [16] These preliminary investigations have shown that this emergent de-icing technology deserves particular attention due to its energetic (low-power consumption) and environmentally favorable (no need for toxic de-icing lubricants) characteristics. However, to prepare the method for exploitation in real-world scenarios, advances are required in critical aspects, such as the activation of much larger surfaces and the use of IDT apertures in the centimeter scale, in contrast to usual SAW devices, where maximum apertures are in the order of a few millimeters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the ice thickness tests, SAW device 1 was cooled along with the chamber at RH = 100% (i.e., by blowing with cold humid air) and different temperatures of −10, −20, −30, and −40 °C. The thickness of rime ice (formed from small droplets or fogs of water with a rough, opaque surface and brittle tissue) 38 was estimated by weighing the mass of the device before and immediately after the icing process at 1 min intervals. To do different ice type tests, SAW devices 5 and 6 were cooled in the chamber with RH = 80% and the temperature was set at −10 °C, and then the glaze ice (formed from large droplets with smooth, transparent surfaces and dense tissues) 38 was formed by freezing a deionized water droplet on the SAW devices' surface within a poly(dimethylsiloxane) chamber (with internal and external sizes of 55 × 30 × 5 mm and 65 × 40 × 5 mm, respectively) and further frozen for 10 min to increase the adhesion process.…”
Section: Characterization Of Saw Sensors In Cold Environmentsmentioning
confidence: 99%
“…As seen from Table , ultrasonic and acoustic wave technologies are two promising candidates to monitor ice/frost formation in a cold environment, and they are commonly based on monitoring of the vibration frequencies with the capability of ice thickness measurement. ,, Another key advantage of these techniques is that they can also be used as active deicing or antiicing methods. For example, recent studies clearly show that, for ice mitigation, surface-acoustic-wave (SAW) devices can generate both acoustic wave vibrations and thermal effects on the device surface, , thus offering great potential for both antiicing and deicing with a reasonably high efficiency. Therefore, it could be applied as one of the appropriate techniques for effectively tackling icing issues on structural surfaces. However, the conventionally used bulk piezoelectric ceramic-based ultrasonic or SAW devices have critical issues such as brittleness of the piezoelectric substrates (especially at high acoustic wave powers or large mechanical forces), rigidity, and noncompatibility with structural surfaces or microelectrics-based mass production technologies.…”
Section: Introductionmentioning
confidence: 99%